Serum antibody immunoreactivity and safety of native porcine and recombinant zona pellucida vaccines formulated with a non-Freund's adjuvant in horses. Issue 10 (28th February 2019) - Nolan, Margaret B.; Schulman, Martin L.; Botha, Alma E.; Human, Anne-Marie; Roth, Robyn; Crampton, Michael C.; Bertschinger, Henk J.
Highlights: Recombinant zona pellucida vaccination in horse mares is immunologically effective. A non-Freund's adjuvant is effective for zona pellucida immunocontraception. Side effects are minimal and transient. Anti-zona pellucida antibody titres are associated with ovarian activity in mares. Abstract: Commercial and regulatory limitations associated with native porcine zona pellucida (pZP) vaccines formulated with Freund's adjuvants may be overcome by developing effective recombinant ZP vaccines (reZP) and identifying alternative adjuvant formulations. A two-part preparatory study used 15 geldings and identified potentially effective alternative adjuvant formulations based on anti-pZP antibody response following treatment with pZP formulated with Addavax (AddaVax ™, Invivogen), Quil A (Quil-A® Adjuvant, Invivogen), Quil A and Poly (I:C) (HMW VacciGrade™, Invivogen), Pet Gel A (Montanide™ Pet Gel A, Seppic) and Pet Gel A and Poly (I:C). Injection site reactions, rectal temperature and respiratory and heart rates were also monitored for three days post-treatment. Suitable anti-pZP antibody titres were seen in response to Pet Gel A and Pet Gel A and Poly (I:C). Subsequently in 31 mares, following administration of pZP, reZP and a combination of pZP and reZP proteins prepared in Pet Gel A and Poly (I:C), both serum anti-pZP and -reZP antibody responses were monitored. In addition, safety was assessed for up to seven days post-treatment by inspection and palpation of gluteal intramuscular injection sites and measurement of rectal temperature. The measured antibody titres in all treatment groups differed significantly to an adjuvant control group (P < 0.001). Temporal changes in both anti-pZP and -reZP antibody titres in all ZP treatment groups were similar to patterns reported previously in various species vaccinated with pZP formulated with Freund's adjuvants. There were no differences in anti-pZP antibody titres between the pZP and reZP treated groups (P > 0.05). Side effects were mild and transient in nature. This represents the first application of a reZP vaccine formulated with non-Freund's adjuvants evoking a similar antibody titre response to native pZP vaccination in mares.